2023
DOI: 10.3390/cells12020336
|View full text |Cite
|
Sign up to set email alerts
|

Erk1/2-Dependent HNSCC Cell Susceptibility to Erastin-Induced Ferroptosis

Abstract: Unfavorable clinical outcomes mean that cancer researchers must attempt to develop novel therapeutic strategies to overcome therapeutic resistance in patients with HNSCC. Recently, ferroptosis was shown to be a promising pathway possessing druggable targets, such as xCT (SLC7A11). Unfortunately, little is known about the molecular mechanisms underlying the susceptibility of HNSCC cells to ferroptosis. The goal of this study was to determine whether HNSCC cells with activated Erk1/2 are vulnerable to ferroptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…The results of this study corroborate the previous reports that have highlighted the importance of SOD2 in buffering superoxide accumulation, as well as dictating sensitivity to chemotherapy and pro-ferroptosis agents [7,25,26]. Specifically, our study showed that the depletion of SOD2 in TMZ-resistant GBM cells re-sensitized them to erastin-mediated ferroptosis, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study corroborate the previous reports that have highlighted the importance of SOD2 in buffering superoxide accumulation, as well as dictating sensitivity to chemotherapy and pro-ferroptosis agents [7,25,26]. Specifically, our study showed that the depletion of SOD2 in TMZ-resistant GBM cells re-sensitized them to erastin-mediated ferroptosis, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…It has been known that the major form of ROS produced within mitochondria is superoxide [8]. Previous studies have shown that decreased cellular antioxidant capacity, such as SOD2 levels, contributes to ferroptosis [26,27]. The antioxidative function of SOD2 is located within the mitochondrial matrix, where it converts superoxide anions produced by mitochondria during electron transport chain (ETC) to a less harmful radical, hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation